THE PSYCHOLOGICAL WELL-BEING OF INTERNATIONAL BUSINESS TRAVELLERS FROM THE GENDER PERSPECTIVE - Kerttula, Sini (My University, 2018)
The number of business trips increases constantly due to globalization, thus making international business travellers (IBTs) valuable resource. IBTs refer to employees whose jobs require travelling abroad. Business trips seem to include both, ups and downs, which all affect the travelling employees’ well-being. This master’s thesis focuses on examining the effect of gender on IBTs’ psychological well-being, more precisely IBTs’ work engagement (vigor as a core component) and burnout (job exhaustion as a core component). The effect of travelling days and number of international business trips on IBTs’ vigor and exhaustion levels is also studied. The theoretical framework is based on work engagement, job burnout, and situational and personal factors. Travelling days and number of business trips are part of situational factors that are considered as both, a job resource (i.e. cause of vigor) and demand (i.e. cause of exhaustion), which is why job demand-resources (JD-R) model is introduced. Gender is considered as personal factor. Data used in this study was collected by web-based questionnaires from the employees of a Finnish software and services company. It was collected by a group of researchers at the University of Vaasa to study the psychological well-being of IBTs’. This thesis focuses on reanalysing part of it (N=372). Results revealed that travelling days and number of business trips have influence on both, IBTs’ vigor and exhaustion. Increase in both predicts exhaustion and vigor among men, whereas for women only increase in number of business trips increases the level of travel related exhaustion. Strongest connections were found between number of business trips and travel related exhaustion with and without gender.
Keywords: International business traveller; psychological well-being; burnout; work engagement; gender; fi=Master's Degree Programme in International Business|